Analysis of Village Financial Management Implementation in Village Fund Allocation (ADD): Analisis Implementasi Pengelolaan Keuangan Desa Dalam Alokasi Dana Desa (ADD) - Hardyanti, Yunita Rachma; Dewi, Santi Rahma (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the application of Village Fund Allocation (ADD) management and the obstacles to implementing Village Fund Allocation (ADD) management in Jiken Village, Tulangan District, Sidoarjo Regency and how to overcome them. This research uses a qualitative approach. This research was conducted by using descriptive analysis method. Data collection was carried out by interview, observation, and documentation. The data analysis was carried out in accordance with the theory put forward by Miles and Hubberman. The results showed that: (1) Village financial management, in this case the Village Fund Allocation (ADD) of Jiken Village, Tulangan District, Sidoarjo Regency, there are several things that are not in accordance with Permendagri No.113 of 2014 concerning village financial management; (2) Constraints in implementing the management of ADD Desa Jiken Ke. Reinforcement District. Sidoarjo is a planning synchronization between the village and sub-district levels; and (3) Limited village allocation funds, as well as a lack of socialization. The way to overcome these obstacles is to coordinate so that village and sub-district planning is synchronized, carry out evaluations regarding the effectiveness and efficiency of ADD, and increase socialization to the community by holding open meetings and other meeting activities so that it can be interspersed with socialization about ADD.